Improving health and safety on construction in Romania. A comparison with Ireland; lessons to be learned - Meekel, Sonya; Paşnicu, Daniela; Jenkins, James L. (Annals of Spiru Haret University. Economic Series, 2011)
The purpose of health and safety procedures in the construction industry is to ensure the health, safety and wellbeing of workers. Due to high accident rates on construction sites internationally, health and safety legislation has focused on minimizing accident causation and promoting construction worker’s safety. However, little attempts has been made to research the effects of those health and safety interventions on the safety behavior on construction sites in Romania. Therefore, the objective of this research was to explore the health and safety improvements on construction sites in Ireland and compare these with the current state-of-play of the construction sector in Romania. Based on the findings in Ireland, an opportunity exists to improve Health and Safety performance on construction sites in Romania. The main findings demonstrate that the safety can be improved through the introduction of safe working systems, enhanced regulation and enforcement, the role of the management and increased staff awareness and training.